2000
DOI: 10.1037/h0088797
|View full text |Cite
|
Sign up to set email alerts
|

Modal profiles for the WISC-III.

Abstract: The present study presents a normative typology for classifying the Wechsler Intelligence Scale for Children-Third Edition (WISC-III) factor index profiles according to profile shape. Q-type principal components analysis of the WISC-III factor index scores identified four profile shapes that were replicated in independent samples. The typology provides good coverage with between 80-85% (depending on classification rule) of participants with significant profile scatter being assigned to a profile type. An initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…Furthermore, this profile shape accounted for an additional 8.8% variance in the prediction of Mathematical Skills over and above general profile level, which supports our hypothesis and is consistent with previous research (e.g., Kim et al, ; Naglieri, ; Pritchard et al, ). The more closely children matched this profile shape, the lower their performance in Mathematical Skills when profile level was controlled.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, this profile shape accounted for an additional 8.8% variance in the prediction of Mathematical Skills over and above general profile level, which supports our hypothesis and is consistent with previous research (e.g., Kim et al, ; Naglieri, ; Pritchard et al, ). The more closely children matched this profile shape, the lower their performance in Mathematical Skills when profile level was controlled.…”
Section: Discussionsupporting
confidence: 92%
“…Critics of the interpretation of intraindividual differences or profile shape analysis have pointed to the finding that profile shape or pattern does not add incremental validity to the prediction of educational outcomes, once profile level is accounted for (e.g., Kahana et al, 2002;Watkins & Glutting, 2000). Other studies showed that profile shape contributes to the prediction of educational outcomes, over and above the effect of profile level (Kim et al, 2004;Naglieri, 2000;Pritchard et al, 2000;Rohde & Thompson, 2007). In the present study, profile level was expected to be the strongest predictor of Mathematical Skills, but profile shape was hypothesized to add incremental validity, especially when meaningful subtest variation is present.…”
Section: Intraindividual Differences In Cognitive and Motivational Vamentioning
confidence: 99%
“…MPA yields clusters that vary in terms of profile shape. MPA identifies the most frequently occurring profile patterns in a dataset, which are then compiled to create the "modal" profiles (Pritchard, Livingston, Reynolds, & Moses, 2000;Skinner & Lei, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Modal profile analysis relies on standardized scores to yield clusters that vary in terms of profile shape. It identifies the most frequently occurring profile patterns in the data and compiles them to create normative profiles (Pritchard et al, 2000). One limitation of cluster analysis in comparison to MDS is that the clusters describe individual differences in overall profile level, rather than individual differences in profile patterns (Kim et al, 2004).…”
Section: Personality Profile Construction and Mdsmentioning
confidence: 99%